Cytokine Profile of Invasive Pulmonary Aspergillosis in Severe COVID-19 and Possible Therapeutic Targets - Alessandro Russo; Helen Linda Morrone; Salvatore Rotundo; Enrico Maria Trecarichi; Carlo Torti (Diagnostics, 2022)
During the SARS-CoV-2 pandemic, a higher incidence of invasive pulmonary aspergillosis was observed in patients affected by Coronavirus disease 2019 (COVID-19), leading to the delineation of a new entity named COVID-19 associated pulmonary aspergillosis (CAPA). A predisposition to invasive infection caused by Aspergillus spp. in SARS-CoV-2 infected patients can be ascribed either to the direct viral-mediated damage of the respiratory epithelium, as already observed in influenza H1N1 virus infections, or to the dysregulated immunity associated with COVID-19. This narrative review focuses on the impact of immune impairment, particularly due to cytokine dysregulation caused by Aspergillus spp. superinfection in COVID-19 for a more in-depth understanding of the molecular pathways implicated in CAPA. As immune competence has proven to be essential in protecting against CAPA onset, a role already threatened by SARS-CoV-2 infection itself, preventive strategies should focus on reducing factors that could further target the host immune system. We also aimed to focus on well-known and less-known risk factors for IPA in COVID-19 patients, related to the main causes of immune suppression, both virus-mediated and iatrogenic, including treatments currently indicated for COVID-19. Lastly, possible preventive strategies aimed at reducing morbidity and mortality due to CAPA could be implemented.